A Case of Massive Metoprolol Overdose Successfully Managed - Bala, Poppy; Ali, Atahar; Rahman, Kazi Atiqur; Islam, Nighat; Khan, Mahmood Hasan (Bangladesh Heart Journal, 2020)
Abstract Not Available Bangladesh Heart Journal 2020; 35(1) : 71-73